Influence of Particle-Size Distribution and Temperature on Rheological Behavior of Coal Slurry. Issue 1 (2nd January 2016) - Singh, Mani Kanwar; Ratha, Dwarikanath; Kumar, Satish; Kumar, Deepak
Abstract : The rheological behavior of coal-water slurry of Indian coal is studied using rheometer. The effect of particle size, solid concentration, and temperature on the rheology of the coal-water slurry has been investigated. The settlement analysis of various size ranges of coal particles has been carried out. A particle size less than 75 µm is used for analysis of rheological behavior of coal slurry and it is found that the increase in solid concentration caused the increase in apparent viscosity of the coal-water mixture. Also, it is observed that as the solid concentration increases the coal-water mixture converts to a non-Newtonian fluid. The rheological behavior of the slurry is also analyzed by blending the coal samples with mixture of coarse and fine particles, hence making a bimodal particle-size distribution. The slurry having the bimodal particle-size distribution is prepared by blending the fine particles of 53–75 µm with the coarse particles of 106–150 µm or 150–250 µm with various proportions. The optimum fraction obtained in bimodal slurry sample is 30% at which point the apparent viscosity is minimum. The change in the flow behavior of coal slurries are fitted to rheological models and the model parameters are calculated.